Physico-chemical Characteristics and Fighting Fish Species in Swamp Waters of Sawah Village, Kampar Utara District, Kampar Regency, Riau Province - Nasir, Abdini Ulfa; Fajri, Nur El; Yuliati, Yuliati (Jurnal Perikanan dan Kelautan, 2023)
Sawah Village Swamp is one of the swamp waters in Kampar Utara District, Kampar Regency, Riau Province, as a habitat for fighting fish. This study aimed to determine the existing conditions of water quality, type, and population of fighting fish. The research method used is the survey method. Determination of sampling points using a purposive sampling method. The data results measuring the existing conditions of the quality of swamp waters in Sawah Village can still support aquatic organisms, especially fighting fish. The types of fighting fish found during the study consisted of 4 types: Trichopsis vittata, Betta akarensis, Betta waseri, and Betta imbellis. The number decreases if fishing efforts continue to be increased.